An Influence Of Financial Literacy And Demographic Factors On Retirement Planning Of Millennials In Gujarat. - Riddhi Adthakkar (Educational Administration: Theory and Practice, 2024)
The research aims to examine the influence of financial literacy and demographic factors on retirement planning of millennials. The key variables studied are financial literacy, financial knowledge and attitude of investors. A quantitative approach was adopted and data was collected through questionnaires from a sample of 50 millennials in Gujarat. The data collected was analyzed using SPSS software to test the hypothesized relationship. It wants to checks whether financial literacy has a direct or indirect relationship with retirement planning. The study provides insights and highlights the need for retirement planning by millennials.